Premature Cognitive Commitment between Divorced Mothers and Daughters in the Early 2000s in South Korea: A Qualitative Study from the Daughters’ Perception - An, Hee-Lan (Journal of Ecohumanism, 2024)
This study explored the premature cognitive commitments of divorced mothers and their daughters toward each other in South Korea in the early 2000s from the daughters’ perception. I conducted in-depth interviews with nine adult women who experienced parental divorce in childhood during the 2002–2004 period, revealing certain premature cognitive commitments that divorced mothers and their daughters had toward each other, such as “I can’t let my mom see that I’m struggling!” and “My daughter comes home late or stays out overnight to hang out with friends owing to her father’s absence.” Based on my findings, I discuss potential implications for counseling divorced families.